Exploring the Link Between Fixed Asset Intensity and Profitability: The Mediating Role of Effective Tax Rate - Duwi Rahayu; Nur Ravita Hanun; Diah Ayu Rintan Sulistiorini; Siti Aisyah (Jurnal Penelitian Ekonomi Akuntansi, 2026)
This study aims to examine the role of the effective tax rate (ETR) as a mediating variable in the influence of fixed asset intensity (FAI) on company profitability. FAI generates depreciation expenses that reduce taxable income, thereby lowering the ETR. This quantitative study uses a sample of 41 state-owned companies (BUMN) in the mining sector that went public during the 2020–2025 period, with a total of 246 financial reports. The data were analyzed using Stata 14 through multiple regression analysis and mediation testing (path analysis/Sobel test). The results of this study show that FAI has a negative effect on profitability and on ETR. ETR also has a negative effect on profitability. Furthermore, ETR mediates the relationship between FAI and profitability, with a negative direction. In conclusion, high FAI lowers the ETR through depreciation expenses. This decrease in ETR then increases after-tax profitability. Thus, ETR mediation is considered effective if the company is able to utilize its fixed assets for tax efficiency to support net income.